Patterns of Strategic Control Within Multinational Corporations - Doz, Yves; Prahalad, C. K. (Journal of International Business Studies, 1984)
The management of multinational operations is often required to balance conflicting priorities between responsiveness at the national subsidiary level and central coordination for global competitiveness. Such balancing requires that relevant data be brought to bear on decisions, that consensus be created among key managers, and that relative power among them be carefully balanced. In large complex MNCs the balancing process can be institutionalized through the structuring of relationships between headquarters and subsidiaries.